Impact of International Fellowship Training Program on Paediatric & Congenital Cardiac Surgery Outcomes In A Low-Income Country - Mehsood, Dawood Kamal; Haq, Intisar Ul; Abdullah , Muhammad; Akram, Adnan; Majid, Muhammad; Nawaz, Atif (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare post procedural mortality and procedural diversity in paediatric and congenital cardiac surgery before and after implementation of an International Fellowship Training Program (IFTP) at a national referral center in a low-income country.Study Design: Comparative cross sectional study designPlace and Duration of Study: Department of Paediatric and Congenital Cardiac Surgery, Armed Forces Institute of Cardiology/ National Institute of Health, Rawalpindi, Pakistan, from January 2014 to December 2023.Methodology: All consecutive patients undergoing Congenital Cardiac surgery falling under Risk Adjustment for Congenital Heart Surgery (RACHS-1) categories II–IV from 2014–2023 were included using universal sampling. Outcomes and procedural distributions were compared between two time-defined cohorts: pre-fellowship training program (2014–2018) and post- fellowship training program (2019–2023). Mortality and procedural distribution were compared between eras.Results: A total of 3388 patients were included. The proportion of high-complexity (RACHS III–IV) operations increased significantly post-fellowship (59.2% vs. 40.8%, p < 0.001). Overall mortality declined from 9.4% to 6.6% (p = 0.004). The biggest improvements occurred in BDG (12.6% to 5.3%, p = 0.01) and ASO (54% to 39%, p < 0.05), while lower-complexity repairs (VSD and TOF) showed smaller yet consistent gains. Conclusion: lower mortality and higher procedural complexity rates were observed in the post-IFTP era compared to the pre-IFTP era at AFIC. Structured exposure to advanced training environments enhances surgical capacity and patient survival in LICs.